2021
DOI: 10.3390/coatings11111400
|View full text |Cite
|
Sign up to set email alerts
|

An Atomization Model of Air Spraying Using the Volume-of-Fluid Method and Large Eddy Simulation

Abstract: When painting complex surfaces, such as large-curvature surfaces, poor coating quality is often obtained, which may be caused by lack of an appropriate atomization model, insufficient understanding of atomization mechanisms and laws, and improper painting parameters. This paper presents a numerical model of paint atomization of air spraying using the volume-of-fluid method and large eddy simulation. The interface capture and the turbulent flow were mainly considered in the model: the former was tracked by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A previously mentioned study [9] selected large eddy simulations for spray turbulence prediction. However, it are found that its computational volume rises sharply with an increase in the number of paint droplets, and thus they considered it not suitable for carrying out the paint atomization simulation with variable parameters.…”
Section: Discussion On Turbulence Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previously mentioned study [9] selected large eddy simulations for spray turbulence prediction. However, it are found that its computational volume rises sharply with an increase in the number of paint droplets, and thus they considered it not suitable for carrying out the paint atomization simulation with variable parameters.…”
Section: Discussion On Turbulence Modelsmentioning
confidence: 99%
“…Moreover, the spatial distribution characteristics of droplet size was obtained through coupling the method of volume of fluid with the discrete phase model (VOF-DPM). Chen et al [9] established an air spray atomization model based on a large eddy simulation and carried out 2D spray atomization simulations. In order to explore the initial atomization liquid film breaking mechanism of the centrifugal nozzles of a rocket motor, Xiang [79] carried out an numerical simulation to explore the initial atomization liquid film breaking mechanism of the centrifugal nozzle based on the VOF and LES method, and a comparison of the high-speed photographic images with the simulation results shows acceptable errors.…”
Section: Research On Atomization Characteristics and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on the film formation model is mainly based on the method of computational fluid dynamics (CFD) now. According to the different treatment methods of paint droplets, there are the Eulerian-Eulerian approach [8][9][10] and the Eulerian-Lagrangian approach [11]. The Eulerian-Lagrangian approach takes the mass, momentum, energy, and compositional exchange between discrete and continuous phases through the physical properties of individual droplets into account.…”
Section: Introductionmentioning
confidence: 99%
“…The droplet-wall impact model can be categorized into four modes: adhesion, rebound, wall-attached jet, and splashing [37,38]. The Weber number can be used as a basis for judging the impact model, and the Weber number is calculated as:…”
mentioning
confidence: 99%